The Empowerment Of Sugar Cane Farmers In Lundo Village Through Syariah Based Cooperation - Sriningsih Sriningsih; Nur Wijawati; Alifah Nur Farindha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
Lundo Village residents in Pati Regency mostly work as sugar cane farmers, where 60% of the total village area was sugar cane farming land. However, many of the sugar cane farmers were still in a state of economic limitations. Nearly 40% of the sugar cane farmers were below the poverty line. Various problems faced by sugar cane farmers consist of: very limited capital access, unavailability of fertilizer on time, inability to master the postharvest technology, not having access to agricultural resources, and having a low bargaining position. In addition, farmers acquired one year to wait for sugar cane to be ready to harvest. To solve this problem, it is necessary a mechanism for managing sugar cane farming in Lundo Village. The solution initiated was through the establishment of a Syariah-based Sugar Cane Cooperative. The cooperative was expected to be able to become a forum for sugar cane farmers and sugar cane laborers to integrate all sugar cane farming activities based on Syariah principles. In order to realize the cooperative, activities are carried out through training with interactive lecture methods and intensive mentoring until the Cooperative formed. The Syariah sugar cane cooperative was built with the expectation of empowering sugar cane farmers and could be a role model for other regions.